Method for manufacturing substrate with cured film, substrate with cured film, photosensitive resin composition, cured film formed by curing photosensitive resin composition, and display device having cured film or substrate with cured film

A photosensitive resin composition with alkali-soluble resins and metal oxide particles forms a cured film with enhanced adhesion and solvent resistance, addressing strength and peeling issues on plastic substrates and organic devices, suitable for display devices.

JP2024174046APending Publication Date: 2024-12-13NIPPON STEEL CHEM & MATERIAL CO LTD

Patent Information

Application Number
JP2024166760
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2019-03-29
Filing Date
2024-09-25
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

Existing photosensitive resin compositions for forming patterns on plastic substrates and organic devices suffer from insufficient film strength, solvent resistance, and adhesion issues, particularly when used at both high and low temperatures, leading to film thinning, surface roughness, and pattern peeling.

Method used

A photosensitive resin composition containing alkali-soluble resins with unsaturated groups, photopolymerizable monomers, and metal oxide fine particles is applied, exposed, and developed to form a cured film pattern, which is then cured at temperatures up to 150°C, ensuring excellent adhesion, solvent resistance, and light scattering properties.

Benefits of technology

The composition achieves a cured film with improved adhesion, solvent resistance, and light scattering properties, suitable for both high and low-temperature applications, enhancing the performance of display devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2024174046000001
    Figure 2024174046000001
  • Figure 2024174046000002
    Figure 2024174046000002
  • Figure 2024174046000003
    Figure 2024174046000003
Patent Text Reader

Abstract

To provide a method for manufacturing a substrate with a cured film.SOLUTION: The method for manufacturing a substrate with a cured film of the present invention is a method for manufacturing a substrate with a cured film by forming a cured film pattern having a light-scattering property on a substrate. In the method, a photosensitive resin composition containing inorganic particles having an average particle diameter of 100 to 700 nm is applied on a substrate, exposed through a photomask, developed to remove an unexposed portion, and heated to form a predetermined cured film pattern.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing a substrate with a cured film, a substrate with a cured film, a photosensitive resin composition, a cured film obtained by curing the photosensitive resin composition, and a display device having the cured film or the substrate with the cured film. [Background technology]

[0002] In recent years, studies have been conducted on forming patterns using photosensitive resin compositions having light-scattering properties not only on highly heat-resistant substrates such as glass substrates and silicon wafers that can be used at high temperatures of 200°C or higher, but also on plastic substrates (plastic films, resin films) such as PET (polyethylene terephthalate) and PEN (polyethylene naphthalate) that have low heat resistance, or on substrates with organic devices such as organic electroluminescence devices and organic TFTs, with the aim of making devices more flexible and one-chip.

[0003] However, when a photosensitive resin composition for forming a pattern by high-temperature baking is baked at a low temperature in accordance with the heat resistance of the substrate, the film strength of the pattern formed on the plastic substrate and the substrate with an organic device becomes insufficient, and there are problems such as film loss of the coating film, surface roughness, pattern peeling, etc., occurring easily in the subsequent steps (e.g., solvent resistance during resist application and alkali resistance during alkali development).

[0004] Therefore, there is a demand for a photosensitive resin composition having light scattering properties that can be used for both high-temperature and low-temperature baking.

[0005] For example, Patent Document 1 discloses a photosensitive composition for forming a pattern having a light scattering function, which is composed of a TiO2 filler, a photopolymerizable (meth)acrylic monomer, an alkali-soluble resin, a photopolymerization initiator, and an organic solvent. The photosensitive composition is said to have photolithography properties suitable for use in a display device, and also has light scattering properties that scatter blue light at angles wider than the incident angle due to the TiO2 filler.

[0006] Patent Document 2 discloses a resin composition for a light scattering layer, which contains at least one resin (A) as a binder material, light scattering particles (B) containing fluorine, and metal oxide particles (C) containing at least one metal oxide particle selected from the group consisting of ZrO2 and TiO2. The resin composition for a light scattering layer is said to have a small wavelength dependency of the light extraction efficiency improvement rate and can be used in a wide wavelength range. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] JP 2013-156304 A [Patent Document 2] JP 2015-022794 A Summary of the Invention [Problem to be solved by the invention]

[0008] However, according to the findings of the present inventors, the photosensitive composition described in Patent Document 1 has low solvent resistance, and the resin composition for a light-scattering layer described in Patent Document 2 could not obtain a pattern having the desired light-scattering properties. Moreover, neither the photosensitive composition described in Patent Document 1 nor the resin composition for a light-scattering layer described in Patent Document 2 fully satisfied the adhesion and linearity reproducibility of the cured film.

[0009] The present invention has been made in consideration of the above points, and has an object to provide a method for manufacturing a substrate with a cured film, a substrate with a cured film, a photosensitive resin composition capable of forming a cured film that has a light scattering function directly on a substrate regardless of the heat resistance temperature of the substrate and is excellent in adhesion, linearity, solvent resistance, etc., a cured film obtained by curing the photosensitive resin composition, and a display device having the cured film and the substrate with the cured film. [Means for solving the problem]

[0010] The method for producing a substrate with a cured film of the present invention is a method for producing a substrate with a cured film by forming a cured film pattern having light scattering properties on a substrate, in which a photosensitive resin composition containing inorganic particles having an average particle size of 100 to 700 nm is applied onto the substrate, exposed through a photomask, and developed to remove unexposed areas, and then heated to form a predetermined cured film pattern.

[0011] The cured film of the present invention is obtained by curing the above-mentioned photosensitive resin composition.

[0012] The substrate with a cured film of the present invention has the above-mentioned cured film.

[0013] The display device of the present invention has the above-mentioned cured film or the above-mentioned substrate with the cured film.

[0014] The method for producing a substrate with a cured film of the present invention is a method for producing a substrate with a cured film by forming a cured film pattern having light scattering properties on a substrate having a heat resistance temperature of 150°C or less, in which the photosensitive resin composition is applied onto the substrate, exposed through a photomask, and developed to remove the unexposed areas, and then heated at 150°C or less to form a predetermined cured film pattern. Effect of the Invention

[0015] According to the present invention, it is possible to provide a method for producing a substrate with a cured film, a substrate with a cured film, a photosensitive resin composition capable of forming a cured film which has a light scattering function directly on a substrate regardless of the heat resistance temperature of the substrate and is excellent in adhesion, linearity, solvent resistance, etc., a cured film obtained by curing the photosensitive resin composition, and a display device having the cured film and the substrate with the cured film. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] Hereinafter, an embodiment of the present invention will be described, but the present invention is not limited to the following embodiment. In addition, in the present invention, when the first decimal place of the content of each component is 0, the notation after the decimal point may be omitted.

[0017] The photosensitive resin composition of the present invention includes (A) an unsaturated group-containing alkali-soluble resin. Any resin can be used without any particular limitation as long as it has an acid value for imparting alkali developability and can be combined with the photopolymerizable monomer of the component (B) to provide appropriate photocurability. Among these resins, generally, resins having a highly aromatic skeleton tend to have a higher specific gravity than aliphatic resins, and can increase the specific gravity of the resin solution when the solution is made at the same resin concentration. It is presumed that this can increase the dispersion stability of metal oxide fine particles, which have a higher specific gravity than the resin. Therefore, by using the resin represented by general formula (1), a photosensitive resin composition having sufficient dispersion stability of metal oxide fine particles can be obtained. Among them, when an unsaturated group-containing alkali-soluble resin (cardo resin) having a polycyclic aromatic skeleton in which X represented by general formula (1) is a fluorene-9,9-diyl group is used, the effect is greater, so it is considered that the dispersion stability of metal oxide fine particles is improved in the cardo resin. This can increase the light scattering property of the cured film obtained by curing the photosensitive resin composition of the present invention. In addition, cardo resins have the property of excellent adhesion during development when forming patterns by photolithography, and it is believed that this property can be effectively utilized even when a filler of metal oxide fine particles is coexisted therewith.

[0018] The mass of the component (A) in the photosensitive resin composition of the present invention is preferably 20 to 70 mass % based on the total mass of the solid contents.

[0019] Here, when the photosensitive resin composition of the present invention is a composition that is baked at a low temperature of 150°C or less, the content of the (A) component is more preferably 20 to 60% by mass based on the total mass of the solid content, and more preferably 35 to 55% by mass when a cardo resin is used. Also, when other resins such as acrylic copolymers are used, it is more preferably 20 to 50% by mass. When the mass of the (A) component is 20% by mass or more based on the total mass of the solid content, even if it contains metal oxide fine particles, it becomes a dissolution development that can stably form a pattern during alkaline development, and it becomes possible to design the composition of the photosensitive resin composition to obtain a desired pattern without residue, and when the mass of the (A) component is 60% by mass or less based on the total mass of the solid content, the definition of the cured film can be improved. Also, the suitability of the production process during alkaline development is improved, and photocurability can be sufficiently guaranteed.

[0020] In addition, when the photosensitive resin composition of the present invention is a composition that is baked at a high temperature of more than 150°C, the content of the (A) component is preferably 35 to 70% by mass based on the total mass of the solid content, and more preferably 45 to 60% by mass when a cardo resin is used. In the case of using other resins such as acrylic copolymers, the content is preferably 35 to 55% by mass or less. When the (A) component content is 35% by mass or more, even if the composition contains metal oxide fine particles, the composition is dissolved and developed during alkaline development, and the desired pattern can be obtained without residue, and when the (A) component content is 70% by mass or less, the definition of the cured film can be improved. In addition, the suitability of the production process during alkaline development is improved, and photocurability can be sufficiently guaranteed.

[0021] The alkali-soluble resin (A) having a carboxy group and a polymerizable unsaturated group in one molecule and represented by the general formula (1) of the present invention can be obtained by reacting a reaction product of an epoxy compound (a-1) having two epoxy groups in one molecule and an unsaturated group-containing monocarboxylic acid with a dicarboxylic acid or tricarboxylic acid or an acid monoanhydride thereof (b), and a tetracarboxylic acid or an acid dianhydride thereof (c).

[0022] [ka]

[0023] (In formula (1), R1, R 2、 R3 and R4 are each independently a hydrogen atom, an alkyl group having 1 to 5 carbon atoms, a halogen atom, or a phenyl group, R5 is a hydrogen atom or a methyl group, X is -CO-, -SO2-, -C(CF3)2-, -Si(CH3)2-, -CH2-, -C(CH3)2-, -O-, a fluorene-9,9-diyl group, or a direct bond, Y is a tetravalent carboxylic acid residue, and Z is each independently a hydrogen atom or a substituent represented by general formula (2). However, at least one of Z is a substituent represented by general formula (2), and n is an integer of 1 to 20.

[0024] [ka]

[0025] (wherein W is a divalent or trivalent carboxylic acid residue, and m is 1 or 2.)

[0026] A method for producing an alkali-soluble resin represented by general formula (1) having a carboxy group and a polymerizable unsaturated group in one molecule (hereinafter simply referred to as "alkali-soluble resin represented by general formula (1)") will be described in detail.

[0027] First, an epoxy compound (a-1) having two epoxy groups in one molecule and represented by general formula (3) (hereinafter simply referred to as "epoxy compound (a-1) represented by general formula (3)") is reacted with an unsaturated group-containing monocarboxylic acid (e.g., (meth)acrylic acid) to obtain an epoxy (meth)acrylate.

[0028] [ka]

[0029] (In formula (3), R1, R 2、R3 and R4 are each independently a hydrogen atom, an alkyl group having 1 to 5 carbon atoms, a halogen atom, or a phenyl group, and X is -CO-, -SO2-, -C(CF3)2-, -Si(CH3)2-, -CH2-, -C(CH3)2-, -O-, a fluorene-9,9-diyl group, or a direct bond.

[0030] The epoxy compound (a-1) represented by the general formula (3) is an epoxy compound having two glycidyl ether groups, which is obtained by reacting a bisphenol with epichlorohydrin.

[0031] Examples of bisphenols used as raw materials for the epoxy compound (a-1) include bis(4-hydroxyphenyl) ketone, bis(4-hydroxy-3,5-dimethylphenyl) ketone, bis(4-hydroxy-3,5-dichlorophenyl) ketone, bis(4-hydroxyphenyl) sulfone, bis(4-hydroxy-3,5-dimethylphenyl) sulfone, bis(4-hydroxy-3,5-dichlorophenyl) sulfone, bis(4-hydroxyphenyl) hexafluoropropane, and bis(4-hydroxy-3,5-dimethylphenyl) hexafluoropropane. propane, bis(4-hydroxy-3,5-dichlorophenyl)hexafluoropropane, bis(4-hydroxyphenyl)dimethylsilane, bis(4-hydroxy-3,5-dimethylphenyl)dimethylsilane, bis(4-hydroxy-3,5-dichlorophenyl)dimethylsilane, bis(4-hydroxyphenyl)methane, bis(4-hydroxy-3,5-dichlorophenyl)methane, bis(4-hydroxy-3,5-dibromophenyl)methane, 2,2-bis(4-hydroxyphenyl)propane, 2,2-bis(4-hydroxy-3,5-dimethylphenyl) 2,2-bis(4-hydroxy-3,5-dichlorophenyl)propane, 2,2-bis(4-hydroxy-3-methylphenyl)propane, 2,2-bis(4-hydroxy-3-chlorophenyl)propane, bis(4-hydroxyphenyl)ether, bis(4-hydroxy-3,5-dimethylphenyl)ether, bis(4-hydroxy-3,5-dichlorophenyl)ether, 9,9-bis(4-hydroxyphenyl)fluorene, 9,9-bis(4-hydroxy-3-methylphenyl)fluorene, 9,9-bis(4-hydroxyphenyl)fluorene, 9,9-bis(4-hydroxy-3-chlorophenyl)fluorene, 9,9-bis(4-hydroxy-3-bromophenyl)fluorene, 9,9-bis(4-hydroxy-3-fluorophenyl)fluorene, 9,9-bis(4-hydroxy-3-methoxyphenyl)fluorene, 9,9-bis(4-hydroxy-3,5-dimethylphenyl)fluorene, 9,9-bis(4-hydroxy-3,5-dichlorophenyl)fluorene, 9,9-bis(4-hydroxy-3,5-dibromophenyl)fluorene, 4,4'-biphenol, 3,3'-biphenol, and the like.These may be used alone or in combination of two or more.

[0032] Examples of the unsaturated group-containing monocarboxylic acid compound include, in addition to acrylic acid and methacrylic acid, compounds obtained by reacting acrylic acid or methacrylic acid with an acid monoanhydride such as succinic anhydride, maleic anhydride, or phthalic anhydride.

[0033] The reaction between the epoxy compound (a-1) represented by the general formula (3) and (meth)acrylic acid can be carried out by a known method. For example, JP-A-4-355450 describes that a diol containing a polymerizable unsaturated group can be obtained by using about 2 moles of (meth)acrylic acid per mole of an epoxy compound having two epoxy groups. In the present invention, the compound obtained by the above reaction is a diol containing a polymerizable unsaturated group, and is a diol (d) containing a polymerizable unsaturated group represented by the general formula (4) (hereinafter, also simply referred to as "diol (d) represented by the general formula (4)").

[0034] [ka]

[0035] (In formula (4), R1, R 2、 R3 and R4 are each independently a hydrogen atom, an alkyl group having 1 to 5 carbon atoms, a halogen atom, or a phenyl group; R5 is a hydrogen atom or a methyl group; and X is -CO-, -SO2-, -C(CF3)2-, -Si(CH3)2-, -CH2-, -C(CH3)2-, -O-, a fluorene-9,9-diyl group, or a direct bond.

[0036] In the production of the alkali-soluble resin represented by general formula (1) by synthesis of the diol (d) represented by general formula (4), the subsequent addition reaction of a polyvalent carboxylic acid or anhydride thereof, and further reaction with a monofunctional epoxy compound having a polymerizable unsaturated group reactive with a carboxy group, the reaction is usually carried out in a solvent using a catalyst as necessary.

[0037] Examples of the solvent include cellosolve-based solvents such as ethyl cellosolve acetate and butyl cellosolve acetate, high-boiling ether or ester-based solvents such as diglyme, ethyl carbitol acetate, butyl carbitol acetate, and propylene glycol monomethyl ether acetate, and ketone-based solvents such as cyclohexanone and diisobutyl ketone. There are no particular limitations on the reaction conditions such as the solvent and catalyst used, but it is preferable to use, for example, a solvent that does not have a hydroxyl group and has a boiling point higher than the reaction temperature as the reaction solvent.

[0038] In addition, it is preferable to use a catalyst in the reaction between a carboxy group and an epoxy group. JP-A-9-325494 describes ammonium salts such as tetraethylammonium bromide and triethylbenzylammonium chloride, and phosphines such as triphenylphosphine and tris(2,6-dimethoxyphenyl)phosphine.

[0039] Next, a diol (d) represented by general formula (4) obtained by reacting an epoxy compound (a-1) represented by general formula (3) with (meth)acrylic acid is reacted with a dicarboxylic acid or tricarboxylic acid or an acid anhydride thereof (b), and a tetracarboxylic acid or an acid dianhydride thereof (c) to obtain an alkali-soluble resin having a carboxy group and a polymerizable unsaturated group in one molecule represented by general formula (1).

[0040] [ka]

[0041] (In formula (1), R1, R 2、R3 and R4 are each independently a hydrogen atom, an alkyl group having 1 to 5 carbon atoms, a halogen atom, or a phenyl group, R5 is a hydrogen atom or a methyl group, X is -CO-, -SO2-, -C(CF3)2-, -Si(CH3)2-, -CH2-, -C(CH3)2-, -O-, a fluorene-9,9-diyl group, or a direct bond, Y is a tetravalent carboxylic acid residue, and Z is each independently a hydrogen atom or a substituent represented by general formula (2). However, at least one of Z is a substituent represented by general formula (2), and n is an integer of 1 to 20.

[0042] [ka]

[0043] (In formula (2), W is a divalent or trivalent carboxylic acid residue, and m is 1 or 2.)

[0044] The acid component used to synthesize the alkali-soluble resin represented by general formula (1) is a polyvalent acid component capable of reacting with the hydroxyl group in the diol (d) molecule represented by general formula (4), and it is necessary to use a dicarboxylic acid or tricarboxylic acid or an acid monoanhydride thereof (b) in combination with a tetracarboxylic acid or an acid dianhydride thereof (c). The carboxylic acid residue of the acid component may be either a saturated or unsaturated hydrocarbon group. In addition, these carboxylic acid residues may contain bonds containing heteroatoms such as -O-, -S-, and carbonyl groups.

[0045] As the dicarboxylic acid or tricarboxylic acid or their monoanhydrides (b), chain hydrocarbon dicarboxylic acids or tricarboxylic acids, alicyclic hydrocarbon dicarboxylic acids or tricarboxylic acids, aromatic hydrocarbon dicarboxylic acids or tricarboxylic acids, or their monoanhydrides, etc. can be used.

[0046] Examples of the acid monoanhydrides of chain hydrocarbon dicarboxylic acids or tricarboxylic acids include acid monoanhydrides of succinic acid, acetylsuccinic acid, maleic acid, adipic acid, itaconic acid, azelaic acid, citramalic acid, malonic acid, glutaric acid, citric acid, tartaric acid, oxoglutaric acid, pimelic acid, sebacic acid, suberic acid, diglycolic acid, etc., and acid monoanhydrides of dicarboxylic acids or tricarboxylic acids having any substituent introduced therein, etc. Examples of the acid monoanhydrides of alicyclic dicarboxylic acids or tricarboxylic acids include acid monoanhydrides of cyclobutanedicarboxylic acid, cyclopentanedicarboxylic acid, hexahydrotrimellitic acid, hexahydrophthalic acid, tetrahydrophthalic acid, norbornanedicarboxylic acid, etc., and acid monoanhydrides of dicarboxylic acids or tricarboxylic acids having any substituent introduced therein, etc. Examples of the acid monoanhydrides of aromatic dicarboxylic acids or tricarboxylic acids include acid monoanhydrides of phthalic acid, isophthalic acid, trimellitic acid, and the like, and acid monoanhydrides of dicarboxylic acids or tricarboxylic acids into which any substituent has been introduced.

[0047] Among the dicarboxylic acid or tricarboxylic acid monoanhydrides, succinic acid, itaconic acid, tetrahydrophthalic acid, hexahydrotrimellitic acid, phthalic acid, and trimellitic acid are preferred, and succinic acid, itaconic acid, and tetrahydrophthalic acid are more preferred.In addition, it is preferred to use the dicarboxylic acid or tricarboxylic acid monoanhydrides thereof.The above-mentioned dicarboxylic acid or tricarboxylic acid monoanhydrides may be used alone or in combination of two or more kinds.

[0048] As the tetracarboxylic acid or its dianhydride (c), a chain hydrocarbon tetracarboxylic acid, an alicyclic hydrocarbon tetracarboxylic acid, an aromatic hydrocarbon tetracarboxylic acid, or their dianhydrides can be used.

[0049] Examples of the chain hydrocarbon tetracarboxylic acid include butane tetracarboxylic acid, pentane tetracarboxylic acid, hexane tetracarboxylic acid, and chain hydrocarbon tetracarboxylic acid having a substituent such as an alicyclic hydrocarbon group or an unsaturated hydrocarbon group introduced therein. Examples of the alicyclic tetracarboxylic acid include cyclobutane tetracarboxylic acid, cyclopentane tetracarboxylic acid, cyclohexane tetracarboxylic acid, cycloheptane tetracarboxylic acid, norbornane tetracarboxylic acid, and alicyclic tetracarboxylic acid having a substituent such as an chain hydrocarbon group or an unsaturated hydrocarbon group introduced therein. Examples of the aromatic tetracarboxylic acid include pyromellitic acid, benzophenone tetracarboxylic acid, biphenyl tetracarboxylic acid, diphenyl ether tetracarboxylic acid, diphenyl sulfone tetracarboxylic acid, and the like.

[0050] Among the tetracarboxylic acids or their dianhydrides, biphenyltetracarboxylic acid, benzophenonetetracarboxylic acid, and diphenylethertetracarboxylic acid are preferred, and biphenyltetracarboxylic acid and diphenylethertetracarboxylic acid are more preferred. In addition, among the tetracarboxylic acids or their dianhydrides, it is preferred to use the dianhydrides. The above-mentioned tetracarboxylic acids or their dianhydrides may be used alone or in combination of two or more.

[0051] The reaction of the diol (d) represented by the general formula (4) with the acid components (b) and (c) is not particularly limited, and any known method can be used. For example, JP-A-9-325494 describes a method in which an epoxy (meth)acrylate is reacted with a tetracarboxylic dianhydride at a reaction temperature of 90 to 140° C.

[0052] Here, it is preferable to react the compound so that the terminals of the compound become carboxy groups, in such a manner that the molar ratio of the diol (d) represented by formula (4), the dicarboxylic acid or tricarboxylic acid or its monoanhydride (b), and the tetracarboxylic acid or its dianhydride (c) is (d):(b):(c)=1:0.01-1.0:0.2-1.0.

[0053] For example, when an acid monoanhydride (b) and an acid dianhydride (c) are used, it is preferable to react them so that the molar ratio [(d) / [(b) / 2+(c)]] of the amount of the acid component to the diol (d) represented by formula (4) is 0.5 to 1.0. Here, when the molar ratio is 1.0 or less, the content of the diol containing unreacted polymerizable unsaturated groups is not increased, so the stability over time of the alkali-soluble resin composition can be improved. On the other hand, when the molar ratio exceeds 0.5, the terminal of the alkali-soluble resin represented by formula (1) does not become an acid anhydride, so that the content of the unreacted acid dianhydride can be suppressed from increasing, so the stability over time of the alkali-soluble resin composition can be improved. In addition, in order to adjust the acid value and molecular weight of the alkali-soluble resin represented by formula (1), the molar ratios of each component (d), (b) and (c) can be arbitrarily changed within the above-mentioned range.

[0054] The acid value of the alkali-soluble resin represented by the general formula (1) is preferably in the range of 20 to 180 mgKOH / g, more preferably 40 mgKOH / g to 140 mgKOH / g, and more preferably 80 mgKOH / g to 120 mgKOH / g. When the acid value is 20 mgKOH / g or more, residues are less likely to remain during alkaline development, and when the acid value is 180 mgKOH / g or less, the penetration of the alkaline developer is not too fast, so peeling development can be suppressed. The acid value can be determined by titration with a 1 / 10N-KOH aqueous solution using a potentiometric titrator "COM-1600" (manufactured by Hiranuma Sangyo Co., Ltd.).

[0055] The weight average molecular weight (Mw) of the alkali-soluble resin represented by the general formula (1) in terms of polystyrene as measured by gel permeation chromatography (GPC) (HLC-8220GPC, manufactured by Tosoh Corporation) is usually 1000 to 100000, preferably 2000 to 20000, and more preferably 2000 to 6000. When the weight average molecular weight is 1000 or more, it is possible to suppress a decrease in the adhesion of the pattern during alkali development. In addition, when the weight average molecular weight is less than 100000, it is easy to adjust the solution viscosity of the photosensitive resin composition to a suitable level for application, and alkali development does not take too long.

[0056] The photosensitive resin composition (B) of the present invention contains a photopolymerizable monomer having at least two ethylenically unsaturated bonds. The component (B) enhances the adhesion of the cured film and enhances the solubility of the exposed area in an alkaline developer to enhance the linearity reproducibility of the cured product. However, in order to prevent the cured film from becoming brittle, and to suppress a decrease in the acid value of the composition, thereby enhancing the solubility of the unexposed area in an alkaline developer, and thus enhancing the linearity reproducibility of the cured product, it is preferable that the amount of the component (B) is not too large.

[0057] Here, when the photosensitive resin composition of the present invention is a composition that is baked at a low temperature of 150° C. or less, the content of component (B) is preferably 5 to 40% by mass based on the total mass of the solid contents. When a cardo resin is used as component (A), the content of component (B) is preferably 5 to 20% by mass based on the total mass of the solid contents. When other acrylic copolymer resins are used as component (A), the content of component (B) is preferably 10 to 35% by mass based on the total mass of the solid contents.

[0058] When the photosensitive resin composition of the present invention is a composition to be baked at a high temperature of more than 150°C, the mass of component (B) is preferably 10 to 40 mass% based on the total mass of the solid content, and when a cardo resin is used as component (A), the mass of component (B) is preferably 10 to 35 mass% based on the total mass of the solid content. When other acrylic copolymer resins are used as component (A), the mass of component (B) is preferably 20 to 40 mass% based on the total mass of the solid content.

[0059] By setting the mass of component (B) to 5 to 40 mass % based on the total mass of solids, it becomes possible to formulate and design a photosensitive resin composition having desired properties, and for example, the linearity and definition of a cured film obtained by curing the photosensitive resin composition of the present invention can be improved.

[0060] Examples of (B) photopolymerizable monomers having at least two ethylenically unsaturated bonds include ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, tetramethylene glycol di(meth)acrylate, glycerol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, trimethylolethane tri(meth)acrylate, pentaerythritol di(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, and the like. (meth)acrylate, dipentaerythritol tetra(meth)acrylate, glycerol tri(meth)acrylate, sorbitol penta(meth)acrylate, dipentaerythritol penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, sorbitol hexa(meth)acrylate, alkylene oxide-modified hexa(meth)acrylate of phosphazene, caprolactone-modified dipentaerythritol hexa(meth)acrylate, and other (meth)acrylic acid esters, as well as compounds having an ethylenic double bond, such as dendritic polymers having a (meth)acryloyl group. These may be used alone or in combination of two or more.

[0061] Examples of dendritic polymers having a (meth)acryloyl group as a compound having an ethylenic double bond include dendritic polymers obtained by adding a polyvalent mercapto compound to a part of the carbon-carbon double bonds in the (meth)acryloyl group of a polyfunctional (meth)acrylate. Specifically, there is a dendritic polymer obtained by reacting a (meth)acryloyl group of a polyfunctional (meth)acrylate represented by general formula (5) with a thiol group of a polyvalent mercapto compound represented by general formula (6).

[0062] [ka]

[0063] (In formula (5), R6 is a hydrogen atom or a methyl group, and R7 is R9(OH) k The remaining portion is the portion in which l hydroxyl groups out of k hydroxyl groups are donated to the ester bond in the formula. k is a polyhydric alcohol based on a non-aromatic straight-chain or branched-chain hydrocarbon skeleton having 2 to 8 carbon atoms, a polyhydric alcohol ether formed by linking a plurality of molecules of the polyhydric alcohol via ether bonds by dehydration condensation of the alcohol, or an ester of such a polyhydric alcohol or polyhydric alcohol ether with a hydroxy acid. k and l are independently integers of 2 to 20, and k≧l.

[0064] [ka]

[0065] (In formula (6), R8 is a single bond or a divalent to hexavalent C1 to C6 hydrocarbon group, and p is 2 when R8 is a single bond, and is an integer from 2 to 6 when R8 is a divalent to hexavalent group.)

[0066] Examples of the polyfunctional (meth)acrylate represented by the general formula (5) include ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, tetramethylene glycol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, ethylene oxide modified trimethylolpropane tri(meth)acrylate, and propylene oxide modified trimethylolpropane tri(meth)acrylate. , trimethylolethane tri(meth)acrylate, pentaerythritol di(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, tripentaerythritol octa(meth)acrylate, tripentaerythritol hepta(meth)acrylate, caprolactone-modified pentaerythritol tri(meth)acrylate, caprolactone-modified Pentaerythritol tetra(meth)acrylate, caprolactone-modified dipentaerythritol hexa(meth)acrylate, epichlorohydrin-modified hexahydrophthalic acid di(meth)acrylate, hydroxypivalic acid neopentyl glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, ethylene oxide-modified neopentyl glycol di(meth)acrylate, propylene oxide-modified neopentyl glycol di(meth)acrylate, ethylene oxide-modified trimethylolpropane Examples of (meth)acrylic acid esters include trimethylolpropane tri(meth)acrylate, propylene oxide modified trimethylolpropane tri(meth)acrylate, trimethylolpropane benzoate (meth)acrylate, tris((meth)acryloxyethyl)isocyanurate, alkoxy modified trimethylolpropane tri(meth)acrylate, dipentaerythritol poly(meth)acrylate, alkyl modified dipentaerythritol tri(meth)acrylate, and ditrimethylolpropane tetra(meth)acrylate. These compounds may be used alone or in combination of two or more.

[0067] Examples of polyvalent mercapto compounds represented by general formula (6) include 1,2-dimercaptoethane, 1,3-dimercaptopropane, 1,4-dimercaptobutane, bisdimercaptoethanethiol, trimethylolpropane tri(mercaptoacetate), trimethylolpropane tri(mercaptopropionate), pentaerythritol tetra(mercaptoacetate), pentaerythritol tri(mercaptoacetate), pentaerythritol tetra(mercaptopropionate), dipentaerythritol hexa(mercaptoacetate), dipentaerythritol hexa(mercaptopropionate), etc. These compounds may be used alone or in combination of two or more.

[0068] In addition, when synthesizing the dendritic polymer, a polymerization inhibitor may be added as necessary. Examples of the polymerization inhibitor include hydroquinone compounds and phenol compounds. Specific examples of these include hydroquinone, methoxyhydroquinone, catechol, p-tert-butylcatechol, cresol, dibutylhydroxytoluene, and 2,4,6-tri-tert-butylphenol (BHT).

[0069] The photosensitive resin composition of the present invention contains an epoxy compound (C). The content of the component (C) is preferably 8 to 24 mass% based on the solid content. When the photosensitive resin composition contains a sufficient amount of the component (C), the solvent resistance of the cured product can be sufficiently increased. However, in order to sufficiently increase the adhesion and linearity reproducibility of the cured product, it is preferable that the amount of the component (C) is not too large.

[0070] For example, when the photosensitive resin composition of the present invention is a composition that is baked at a low temperature of 150° C. or less, the photosensitive resin composition preferably contains a larger amount of component (C). In this case, the mass of component (C) is preferably 8 to 24 mass% based on the solid content, and more preferably 12 to 24 mass% based on the solid content.

[0071] Furthermore, when the photosensitive resin composition of the present invention is a composition that is baked at a high temperature of more than 150° C., the photosensitive resin composition preferably contains a smaller amount of component (C) since component (C) is easily cured sufficiently. In this case, the mass of component (C) is preferably 8 to 20 mass% based on the solid content, and more preferably 8 to 18 mass% based on the solid content.

[0072] Examples of the (C) epoxy compound include bisphenol A type epoxy compounds, bisphenol F type epoxy compounds, bisphenol fluorene type epoxy compounds, phenol novolac type epoxy compounds, cresol novolac type epoxy compounds, phenol aralkyl type epoxy compounds, phenol novolac compounds containing a naphthalene skeleton (e.g., NC-7000L: manufactured by Nippon Kayaku Co., Ltd.), naphthol aralkyl type epoxy compounds, trisphenol methane type epoxy compounds, tetrakisphenol ethane type epoxy compounds, glycidyl ethers of polyhydric alcohols, glycidyl esters of polycarboxylic acids, and (meth)polymers of methacrylic acid and glycidyl methacrylate. Examples of such epoxy compounds include copolymers of monomers having a (meth)acrylic group that contain glycidyl acrylate as a unit, alicyclic epoxy compounds represented by 3',4'-epoxycyclohexylmethyl 3,4-epoxycyclohexanecarboxylate, polyfunctional epoxy compounds having a dicyclopentadiene skeleton (e.g., HP7200 series: manufactured by DIC Corporation), 1,2-epoxy-4-(2-oxiranyl)cyclohexane adducts of 2,2-bis(hydroxymethyl)-1-butanol (e.g., EHPE3150: manufactured by Daicel Corporation), epoxidized polybutadiene (e.g., NISSO-PB JP-100: manufactured by Nippon Soda Co., Ltd.), and epoxy compounds having a silicone skeleton.

[0073] The epoxy equivalent of the epoxy compound of component (C) is preferably 100 to 300 g / eq, more preferably 100 to 200 g / eq. The number average molecular weight (Mn) of the epoxy compound of component (C) is preferably 100 to 5000. These compounds may be used alone or in combination of two or more kinds.

[0074] The epoxy equivalent of the epoxy compound of component (C) can be determined by dissolving the resin solution in dioxane, adding an acetic acid solution of tetraethylammonium bromide, and titrating with a 1 / 10N perchloric acid solution using a potentiometric titrator "COM-1600" (manufactured by Hiranuma Sangyo Co., Ltd.) The number average molecular weight (Mn) of the epoxy compound of component (C) can be determined in terms of polystyrene using gel permeation chromatography (GPC) measurement (HLC-8220GPC, manufactured by Tosoh Corporation).

[0075] The photosensitive resin composition of the present invention preferably contains metal oxide fine particles as component (D). The metal oxide fine particles are preferably inorganic particles having an average particle size of 100 to 700 nm, and more preferably TiO2 particles having an average particle size of 100 to 700 nm.

[0076] The particle size and shape of the TiO2 are not particularly limited as long as the formed cured film (coating film) can exhibit a light scattering function. The average particle size of TiO2 is 100 to 700 nm, and more preferably 200 to 600 nm. When the average particle size of TiO2 is 100 nm or more, the light scattering property of the cured product can be sufficiently increased, and when the average particle size of TiO2 is 700 nm or less, the adhesion and linearity reproducibility of the cured product can be sufficiently increased.

[0077] The average particle size of TiO2 can be determined by the cumulant method using a particle size distribution analyzer "Particle Size Analyzer FPAR-1000" (manufactured by Otsuka Electronics Co., Ltd.) that uses dynamic light scattering.

[0078] Furthermore, component (D) may contain metal oxide fine particles having a refractive index of 1.9 to 2.3 instead of TiO2 having an average particle size of 100 to 700 nm. The particle size and shape of the metal oxide fine particles having a refractive index of 1.9 to 2.3 are not particularly limited as long as the formed cured film (coating film) can exhibit a light scattering function.

[0079] Examples of metal oxide particles having a refractive index of 1.9 to 2.3 include ZnO, ZrO2, etc. Generally, the higher the refractive index of the metal oxide, the higher the light scattering property, but on the other hand, if the light scattering property is too strong, the transmittance of straight light decreases. The refractive index of the metal oxide particles can be measured with an Abbe refractometer using light with a wavelength of 589 nm.

[0080] The average particle size of the ZnO and ZrO2 is preferably 150 to 500 nm, and more preferably 150 to 400 nm. When the average particle size of the metal oxide is 150 nm or more, the light scattering properties of the cured film can be sufficiently improved, and when the average particle size of the metal oxide is 500 nm or less, the adhesion and linearity reproducibility of the cured film can be sufficiently improved.

[0081] The average particle size of the metal oxide fine particles can be determined by the cumulant method using a particle size distribution analyzer "Particle Size Analyzer FPAR-1000" that employs dynamic light scattering.

[0082] The (D) component can improve the light scattering properties of the cured film. However, if the amount of the (D) component contained in the photosensitive resin composition of the present invention is too large, the adhesion, linear reproducibility, definition, and solvent resistance of the cured film will decrease, and the light transmittance of the transmission film will also decrease. Therefore, the mass of the (D) component is preferably 1% by mass or more and 35% by mass or less based on the total mass of the solid content.

[0083] Furthermore, when the photosensitive resin composition of the present invention is a composition that is baked at a low temperature of 150°C or less, the content of component (D) is preferably from 1 mass% to less than 35 mass%, more preferably from 2 mass% to less than 25 mass%, and even more preferably from 2 mass% to less than 20 mass%, relative to the total mass of the solid contents.

[0084] On the other hand, when the photosensitive resin composition of the present invention is a composition that is baked at a high temperature of more than 150°C, the content of the component (D) is preferably 1 mass% or more and less than 35 mass%, and more preferably 2 mass% or more and less than 25 mass%, based on the total mass of the solid contents.

[0085] The photosensitive resin composition of the present invention contains (E) a photopolymerization initiator.

[0086] Examples of the component (E) include acetophenones such as acetophenone, 2,2-diethoxyacetophenone, p-dimethylacetophenone, p-dimethylaminopropiophenone, dichloroacetophenone, trichloroacetophenone, and p-tert-butylacetophenone; benzophenones such as benzophenone, 2-chlorobenzophenone, and p,p'-bisdimethylaminobenzophenone; benzoins such as benzil, benzoin, benzoin methyl ether, benzoin isopropyl ether, and benzoin isobutyl ether. Biimidazole compounds such as 2-(o-chlorophenyl)-4,5-phenylbiimidazole, 2-(o-chlorophenyl)-4,5-di(m-methoxyphenyl)biimidazole, 2-(o-fluorophenyl)-4,5-diphenylbiimidazole, 2-(o-methoxyphenyl)-4,5-diphenylbiimidazole, and 2,4,5-triarylbiimidazole; 2-trichloromethyl-5-styryl-1,3,4-oxadiazole, 2-trichloromethyl-5-(p-cyanostyryl)- Halomethyldiazole compounds such as 1,3,4-oxadiazole and 2-trichloromethyl-5-(p-methoxystyryl)-1,3,4-oxadiazole; 2,4,6-tris(trichloromethyl)-1,3,5-triazine, 2-methyl-4,6-bis(trichloromethyl)-1,3,5-triazine, 2-phenyl-4,6-bis(trichloromethyl)-1,3,5-triazine, 2-(4-chlorophenyl)-4,6-bis(trichloromethyl)-1,3,5-triazine, 2-(4-methoxyphenyl) -Halomethyl-s-triazine compounds such as 4,6-bis(trichloromethyl)-1,3,5-triazine, 2-(4-methoxynaphthyl)-4,6-bis(trichloromethyl)-1,3,5-triazine, 2-(4-methoxystyryl)-4,6-bis(trichloromethyl)-1,3,5-triazine, 2-(3,4,5-trimethoxystyryl)-4,6-bis(trichloromethyl)-1,3,5-triazine, and 2-(4-methylthiostyryl)-4,6-bis(trichloromethyl)-1,3,5-triazine;O-Acyloxime compounds such as 1,2-octanedione, 1-[4-(phenylthio)phenyl]-, 2-(O-benzoyloxime), 1-(4-phenylsulfanylphenyl)butane-1,2-dione-2-oxime-O-benzoate, 1-(4-methylsulfanylphenyl)butane-1,2-dione-2-oxime-O-acetate, 1-(4-methylsulfanylphenyl)butan-1-one oxime-O-acetate; benzyl dimethyl ketal, thioxanthone, 2-chlorothioxanthone, 2,4-diethylthioxanthone Examples of the photopolymerization initiator include sulfur compounds such as 2-ethylanthraquinone, 2-methylthioxanthraquinone, and 2-isopropylthioxanthraquinone; anthraquinones such as 2-ethylanthraquinone, octamethylanthraquinone, 1,2-benzanthraquinone, and 2,3-diphenylanthraquinone; organic peroxides such as azobisisobutyronitrile, benzoyl peroxide, and cumene peroxide; thiol compounds such as 2-mercaptobenzimidazole, 2-mercaptobenzoxazole, and 2-mercaptobenzothiazole; and tertiary amines such as triethanolamine and triethylamine. These photopolymerization initiators may be used alone or in combination of two or more kinds.

[0087] In particular, when a high-sensitivity photopolymerization initiator is required, such as when the amount of metal oxide added is large, when the amount of photopolymerization initiator added is desired to be reduced, or when photocuring is desired to be performed more effectively because a heat curing process at a high temperature such as 150°C cannot be performed, it is preferable to use O-acyloxime compounds (including ketoximes). Among them, the compound group represented by general formula (7) or general formula (8) can be applied as a more sensitive photopolymerization initiator. Among them, when photocuring is desired to be performed more effectively with low-temperature curing, it is more preferable to use an O-acyloxime photopolymerization initiator having a molar absorption coefficient at 365 nm of 10000 L / mol cm or more. In addition, the term "photopolymerization initiator" in the present invention is used to include a sensitizer.

[0088] [ka]

[0089] (In formula (7), R 10 , R 11 each independently represents an alkyl group having 1 to 15 carbon atoms, an aryl group having 6 to 18 carbon atoms, an arylalkyl group having 7 to 20 carbon atoms, or a heterocyclic group having 4 to 12 carbon atoms; R 12 represents an alkyl group having 1 to 15 carbon atoms, an aryl group having 6 to 18 carbon atoms, or an arylalkyl group having 7 to 20 carbon atoms. Here, the alkyl group and the aryl group may be substituted with an alkyl group having 1 to 10 carbon atoms, an alkoxy group having 1 to 10 carbon atoms, an alkanoyl group having 1 to 10 carbon atoms, or a halogen, and the alkylene portion may contain an unsaturated bond, an ether bond, a thioether bond, or an ester bond. In addition, the alkyl group may be any of linear, branched, and cyclic alkyl groups.

[0090] [ka]

[0091] (In formula (8), R 13 and R 14 R are each independently a linear or branched alkyl group having 1 to 10 carbon atoms, a cycloalkyl group, a cycloalkylalkyl group, or an alkylcycloalkyl group having 4 to 10 carbon atoms, or a phenyl group which may be substituted with an alkyl group having 1 to 6 carbon atoms. 15 are each independently a linear or branched alkyl or alkenyl group having 2 to 10 carbon atoms, and some of the -CH2- groups in the alkyl or alkenyl group may be substituted with -O- groups. 13 ~R 15 A part of the hydrogen atoms in the group may be substituted with halogen atoms.

[0092] Here, the mass of the component (E) is preferably 0.1 to 30% by mass, and more preferably 1 to 25% by mass, based on the total mass of the components (A) and (B). When the mass of the component (E) is 0.1% by mass or more based on the total mass of the components (A) and (B), the composition has an appropriate photopolymerization speed, and therefore a decrease in sensitivity can be suppressed. When the mass of the component (E) is 30% by mass or less based on the total mass of the components (A) and (B), the composition is not too sensitive to exposure light, and therefore the line width can be faithfully reproduced on the mask, and the pattern edge can be sharpened.

[0093] The photosensitive resin composition of the present invention contains a solvent (F).

[0094] Examples of the solvent contained in the (F) photosensitive resin composition include alcohols such as methanol, ethanol, n-propanol, isopropanol, ethylene glycol, propylene glycol, 3-methoxy-1-butanol, ethylene glycol monobutyl ether, 3-hydroxy-2-butanone, and diacetone alcohol; terpenes such as α- or β-terpineol; ketones such as acetone, methyl ethyl ketone, cyclohexanone, and N-methyl-2-pyrrolidone; aromatic hydrocarbons such as toluene, xylene, and tetramethylbenzene; cellosolve, methyl cellosolve, ethyl cellosolve, carbitol, methyl carbitol, ethyl carbitol, butyl carbitol, diethylene glycol ethyl methyl ether, and propylene glycol. Examples of the solvent include glycol ethers such as ethylene glycol monomethyl ether, propylene glycol monoethyl ether, dipropylene glycol monomethyl ether, dipropylene glycol monoethyl ether, triethylene glycol monomethyl ether, and triethylene glycol monoethyl ether; and esters such as ethyl acetate, butyl acetate, ethyl lactate, 3-methoxybutyl acetate, 3-methoxy-3-butyl acetate, cellosolve acetate, ethyl cellosolve acetate, butyl cellosolve acetate, carbitol acetate, ethyl carbitol acetate, butyl carbitol acetate, propylene glycol monomethyl ether acetate, and propylene glycol monoethyl ether acetate. By dissolving and mixing using these, a homogeneous solution-like composition can be obtained. These solvents may be used alone or in combination of two or more to obtain the required characteristics such as coatability.

[0095] The content of the component (F) varies depending on the target viscosity, but is preferably 60 to 90% by mass in the photosensitive resin composition solution.

[0096] The photosensitive resin composition of the present invention may contain (G) a curing agent and / or a curing accelerator for the epoxy compound. When the photosensitive resin composition of the present invention is a composition that is baked at a low temperature of 150° C. or less, the curing of the component (C) is likely to be insufficient, so the photosensitive resin composition preferably contains the component (G) in order to sufficiently cure the component (C).

[0097] Examples of the curing agent for the epoxy compound, which is the component (G), include amine compounds, polycarboxylic acid compounds, phenol resins, amino resins, dicyandiamide, Lewis acid complex compounds, etc. In the present invention, polycarboxylic acid compounds can be preferably used.

[0098] Examples of polycarboxylic acid compounds include polycarboxylic acids, polycarboxylic anhydrides, and polycarboxylic heat decomposable esters. Polycarboxylic acids refer to compounds having two or more carboxy groups in one molecule, such as succinic acid, maleic acid, cyclohexane-1,2-dicarboxylic acid, cyclohexene-1,2-dicarboxylic acid, cyclohexene-4,5-dicarboxylic acid, norbornane-2,3-dicarboxylic acid, phthalic acid, 3,6-dihydrophthalic acid, 1,2,3,6-tetrahydrophthalic acid, methyltetrahydrophthalic acid, benzene-1,2,4-tricarboxylic acid, cyclohexane-1,2,4-tricarboxylic acid, benzene-1,2,4,5-tetracarboxylic acid, cyclohexane-1,2,4,5-tetracarboxylic acid, butane-1,2,3,4-tetracarboxylic acid, etc. Examples of polycarboxylic acid anhydrides include the acid anhydrides of the above compounds. These may be intermolecular acid anhydrides, but generally, acid anhydrides that are ring-closed within a molecule are used. Examples of the thermally decomposable esters of polycarboxylic acids include t-butyl esters, 1-(alkyloxy)ethyl esters, and 1-(alkylsulfanyl)ethyl esters of the above compounds (wherein alkyl is a saturated or unsaturated hydrocarbon group having 1 to 20 carbon atoms, and the hydrocarbon group may have a branched or cyclic structure and may be substituted with any substituent). In addition, polymers or copolymers having two or more carboxy groups can also be used as the polycarboxylic acid compound, and the carboxy groups may be anhydrides or thermally decomposable esters.

[0099] Examples of the polymer or copolymer include a polymer or copolymer containing (meth)acrylic acid as a constituent, a copolymer containing maleic anhydride as a constituent, and a compound obtained by reacting a tetracarboxylic dianhydride with a diamine or diol to open the ring of the acid anhydride. Of these, it is preferable to use anhydrides of phthalic acid, 3,6-dihydrophthalic acid, 1,2,3,6-tetrahydrophthalic acid, methyltetrahydrophthalic acid, and benzene-1,2,4-tricarboxylic acid. When a polycarboxylic acid compound is used as a curing agent for an epoxy compound, the compounding ratio is preferably such that the carboxyl group of the polycarboxylic acid compound is 0.5 to 1.5 mol, more preferably 0.6 to 1.2 mol, per 1 mol of the epoxy group of the epoxy compound.

[0100] As the curing accelerator for the epoxy compound, which is the component (G), known compounds known as curing accelerators for epoxy compounds, curing catalysts, latent curing agents, etc. can be used. Examples of the curing accelerator for the epoxy compound include tertiary amines, quaternary ammonium salts, tertiary phosphines, quaternary phosphonium salts, boric acid esters, Lewis acids, organometallic compounds, imidazoles, etc. Among the above curing accelerators, 1,8-diazabicyclo[5.4.0]undec-7-ene or 1,5-diazabicyclo[4.3.0]non-5-ene or salts thereof are preferred.

[0101] The amount of the curing accelerator is preferably 0.05 parts by mass or more and 2 parts by mass or less with respect to 100 parts by mass of the epoxy compound. When the amount of the curing accelerator is 0.05 parts by mass or more, the amount can be adjusted depending on the state of expression of the chemical resistance of the resin film pattern after thermal curing. In addition, when the amount of the curing accelerator is 2 parts by mass or less, the curing speed of the epoxy compound can be set in an appropriate range.

[0102] When the photosensitive resin composition of the present invention is a composition that is baked at a low temperature of 150° C. or less, the total mass of the (C) component and the (G) component is preferably 15% by mass or more and 35% by mass or less, more preferably 20% by mass or more and 30% by mass or less, based on the total mass of the solid content. When the total mass of the (C) component and the (G) component is 15% by mass or more based on the total mass of the solid content, the curability is sufficiently guaranteed when cured at a low temperature of 150° C. or less. In addition, when the total mass of the (C) component and the (G) component is 35% by mass or less based on the total mass of the solid content, the curability can be improved without adversely affecting the patterning property, linearity, and solvent resistance during alkaline development.

[0103] When the photosensitive resin composition of the present invention is a composition that is baked at a high temperature of more than 150°C, the component (G) is not necessary, and the total mass of the components (C) and (G) is preferably 8 to 25 mass% based on the total mass of the solid contents.

[0104] Next, a method for producing a plurality of substrates with a cured film of the present invention will be described. The cured film (coating film) of the present invention can be formed by a photolithography method using the photosensitive resin composition of the present invention.

[0105] The method for producing a substrate with a cured film by forming a cured film pattern having light scattering properties on a substrate of the present invention is a production method in which a photosensitive resin composition containing inorganic particles having an average particle size of 100 to 700 nm is applied onto a substrate, exposed to light through a photomask, developed to remove unexposed areas, and heated to form a predetermined cured film pattern.

[0106] The method of the present invention for producing a substrate with a cured film by forming a cured film pattern having light scattering properties on a substrate having a heat resistance temperature of 150°C or less is a production method comprising applying the above-mentioned photosensitive resin composition onto a substrate, exposing the substrate to light through a photomask, removing the unexposed areas by development, and heating the substrate at a temperature of 150°C or less to form a predetermined cured film pattern.

[0107] The method of the present invention for producing a substrate with a cured film by forming a cured film pattern having light scattering properties on a substrate having a heat resistance temperature of more than 150°C is a production method in which the above-mentioned photosensitive resin composition is applied onto a substrate, exposed to light through a photomask, and developed to remove unexposed areas, and then heated at a temperature of more than 150°C to form a predetermined cured film pattern.

[0108] The photosensitive resin composition of the present invention can be applied to a substrate by any method, including known solution immersion and spraying methods, as well as methods using a roller coater, land coater, slit coater, or spinner. After application to a desired thickness by these methods, the solvent is removed (prebaked) to form a coating. Prebaking is performed by heating in an oven, a hot plate, or the like. The heating temperature and heating time in prebaking are appropriately selected depending on the solvent used, and are performed, for example, at a temperature of 60 to 110°C (set so as not to exceed the heat resistance temperature of the substrate) for 1 to 3 minutes.

[0109] The exposure performed after the pre-baking is performed by an ultraviolet exposure device, and only the resist in the portion corresponding to the pattern is exposed by exposing through a photomask. The exposure device and its exposure irradiation conditions are appropriately selected, and the exposure is performed using a light source such as an ultra-high pressure mercury lamp, a high pressure mercury lamp, a metal halide lamp, or a far ultraviolet lamp, to photocure the photosensitive resin composition in the coating film. Preferably, the photocure is performed by irradiating a certain amount of light with a wavelength of 365 nm.

[0110] Examples of radiation used for exposure include visible light, ultraviolet light, far ultraviolet light, electron beams, and X-rays, and the wavelength range of the radiation is preferably 250 to 450 nm. Examples of developers suitable for this alkaline development include aqueous solutions of sodium carbonate, potassium carbonate, potassium hydroxide, diethanolamine, and tetramethylammonium hydroxide. These developers can be appropriately selected according to the characteristics of the resin layer, and surfactants may be added as necessary. The development temperature is preferably 20 to 35°C, and fine images can be precisely formed using a commercially available developing machine or ultrasonic cleaner. After alkaline development, the film is usually washed with water. Examples of development methods that can be used include shower development, spray development, dip (immersion) development, and puddle (liquid puddle) development.

[0111] The alkaline development after exposure is carried out for the purpose of removing the resist in the unexposed portion, and the desired pattern is formed by this development. Examples of the developer suitable for this alkaline development include an aqueous solution of carbonate of an alkali metal or an alkaline earth metal, an aqueous solution of hydroxide of an alkali metal, etc., but it is particularly preferable to use a weakly alkaline aqueous solution containing 0.05 to 3.0 mass % of carbonate such as sodium carbonate, potassium carbonate, or lithium carbonate at a temperature of 23 to 28°C, and fine images can be precisely formed using a commercially available developing machine, ultrasonic cleaner, etc.

[0112] When a cured film pattern having light scattering properties is formed on a substrate having a heat resistance of 150°C or less, after development, a heat treatment (post-baking) is preferably performed at a temperature of 80 to 140°C (set so as not to exceed the heat resistance temperature of the substrate) for 20 to 90 minutes, more preferably at a temperature of 90 to 120°C for a heating time of 30 to 60 minutes. The post-baking is performed for the purpose of increasing the adhesion between the patterned cured film and the substrate. This is performed by heating in an oven, a hot plate, or the like, as in the pre-baking. The patterned cured film of the present invention is formed through each step of the photolithography method described above.

[0113] When a cured film pattern having light scattering properties is formed on a substrate having a heat resistance of more than 150°C, it is preferable to perform a heat treatment (post-baking) after development at a temperature of 80 to 250°C (set so as not to exceed the heat resistance temperature of the substrate) for 20 to 90 minutes, and more preferably at a temperature of 180 to 230°C and for a heating time of 30 to 60 minutes. The post-baking is performed for the purpose of increasing the adhesion between the patterned cured film and the substrate. This is performed by heating in an oven, a hot plate, or the like, as in the pre-baking. The patterned cured film of the present invention is formed through each step of the photolithography method described above.

[0114] The above method can provide a cured film obtained by curing a photosensitive resin composition containing TiO2 with an average particle size of 100 to 700 nm as the component (D), and a substrate with a cured film having a visible light transmittance of 70% or more, and in which, when white light is irradiated perpendicularly to the substrate with the cured film, the intensity of the scattered light at 60° is 20% or more of the intensity of the scattered light at 5° when the angle of the directly transmitted light that travels straight without scattering is set to 0°. Therefore, the substrate can be suitably used as a light scattering layer in a display device.

[0115] The above method can provide a cured film obtained by curing a photosensitive resin composition containing a metal oxide (ZnO, ZrO2) with a refractive index of 1.9 to 2.3 as the component (D), and a substrate with a cured film in which the intensity of scattered light at 45° is 15% or more of the intensity of scattered light at 5° when the angle at which the transmittance in the visible light region is 80% is taken as 0°. Therefore, the cured film can be suitably used in a display device as a light scattering layer. EXAMPLES

[0116] Hereinafter, the embodiments of the present invention will be described in detail based on examples and comparative examples, but the present invention is not limited to these.

[0117] First, the synthesis examples of the alkali-soluble resin represented by the general formula (1) will be described. The resins in these synthesis examples were evaluated as follows unless otherwise specified. When the same model of measuring equipment was used, the name of the equipment manufacturer is omitted from the second position. In addition, in Examples 1 and 2, the glass substrates used to prepare the substrates with the cured film for measurement were all glass substrates that had been subjected to the same treatment.

[0118] [Solid content concentration] 1 g of the resin solution obtained in Synthesis Example was impregnated into a glass filter (weight: W0(g)), weighed [W1(g)], and the weight after heating at 160°C for 2 hours [W2(g)] was calculated from the following formula. Solid content concentration (weight%) = 100 × (W2-W0) / (W1-W0)

[0119] [Epoxy equivalent] The resin solution was dissolved in dioxane, and then a solution of tetraethylammonium bromide in acetic acid was added. The content was determined by titration with a 1 / 10N perchloric acid solution using a potentiometric titrator "COM-1600" (manufactured by Hiranuma Sangyo Co., Ltd.).

[0120] [Acid value] The resin solution was dissolved in dioxane and titrated with a 1 / 10N KOH aqueous solution using a potentiometric titrator "COM-1600" to determine the content.

[0121] [Molecular weight] Measurement was performed using gel permeation chromatography (GPC) "HLC-8220GPC" (solvent: tetrahydrofuran, columns: TSKgelSuperH-2000 (2 columns) + TSKgelSuperH-3000 (1 column) + TSKgelSuperH-4000 (1 column) + TSKgelSuperH-5000 (1 column) (manufactured by Tosoh Corporation), temperature: 40°C, speed: 0.6 ml / min), and the weight average molecular weight (Mw) was calculated as a value converted into standard polystyrene (manufactured by Tosoh Corporation, PS-oligomer kit).

[0122] [Average particle size] The particle size distribution was determined by the cumulant method using a dynamic light scattering particle size analyzer "Particle Size Analyzer FPAR-1000."

[0123] The abbreviations used in the synthesis examples are as follows. DCPMA: dicyclopentanyl methacrylate GMA: Glycidyl methacrylate St: styrene AA: Acrylic acid SA: Succinic anhydride BPFE: Bisphenol fluorene type epoxy compound (reaction product of 9,9-bis(4-hydroxyphenyl)fluorene and chloromethyloxirane) BPDA: 3,3',4,4'-biphenyltetracarboxylic dianhydride THPA: Tetrahydrophthalic anhydride PTMA: Pentaerythritol tetra(mercaptoacetate) DPHA: Mixture of dipentaerythritol pentaacrylate and hexaacrylate TEAB: Tetraethylammonium bromide AIBN: Azobisisobutyronitrile TDMAMP: Trisdimethylaminomethylphenol HQ: Hydroquinone TEA: Triethylamine BzDMA: benzyldimethylamine PGMEA: Propylene glycol monomethyl ether acetate

[0124] [Synthesis Example 1] BPFE (114.4g, 0.23 mol), AA (33.2g, 0.46 mol), PGMEA (157g) and TEAB (0.48g) were charged into a 500ml four-neck flask equipped with a reflux condenser, and the mixture was stirred at 100-105°C for 20 hours to react. Next, BPDA (35.3g, 0.12 mol) and THPA (18.3g, 0.12 mol) were charged into the flask, and the mixture was stirred at 120-125°C for 6 hours to obtain a polymerizable unsaturated group-containing alkali-soluble resin (A)-1. The solid content concentration of the obtained resin solution was 56.1% by mass, the acid value (solid content equivalent) was 103mgKOH / g, and the weight average molecular weight (Mw) by GPC analysis was 3600.

[0125] [Synthesis Example 2] PGMEA (300 g) was placed in a 1 L four-neck flask equipped with a reflux condenser, and the flask was purged with nitrogen and then heated to 120° C. A monomer mixture (DCPMA (77.1 g, 0.35 mol), GMA (49.8 g, 0.35 mol), St (31.2 g, 0.30 mol) dissolved in AIBN (10 g) was added dropwise from a dropping funnel to the flask over 2 hours, and the mixture was stirred at 120° C. for another 2 hours to obtain a copolymer solution.

[0126] Next, after replacing the inside of the flask system with air, AA (24.0 g (95% of glycidyl group), TDMAMP (0.8 g) and HQ (0.15 g) were added to the obtained copolymer solution and stirred at 120 ° C for 6 hours to obtain a polymerizable unsaturated group-containing copolymer solution. Furthermore, SA (30.0 g (90% of AA added moles)) and TEA (0.5 g) were added to the obtained polymerizable unsaturated group-containing copolymer solution and reacted at 120 ° C for 4 hours to obtain a polymerizable unsaturated group-containing alkali-soluble copolymer resin solution (A)-2. The solid content concentration of the resin solution was 41.7 mass%, the acid value (solid content equivalent) was 76 mg KOH / g, and the weight average molecular weight (Mw) by GPC analysis was 5300.

[0127] [Synthesis Example 3] PTMA (20 g, mercapto group 0.19 mol), DPHA (212 g, acrylic group 2.12 mol), PGMEA (58 g), HQ (0.1 g), and BzDMA (0.01 g) were added to a 1 L four-neck flask and reacted at 60°C for 12 hours to obtain dendritic polymer solution (B)-3 (solid content concentration: 80 mass%). The disappearance of thiol groups in the obtained dendritic polymer was confirmed by iodometry. The weight average molecular weight (Mw) of the obtained dendritic polymer was 10,000.

[0128] The abbreviations shown in Tables 1, 2, 4, 5, 7, 8, 10, and 11 are as follows.

[0129] (Polymerizable unsaturated group-containing alkali-soluble resin) (A)-1: Resin solution obtained in Synthesis Example 1 above (solid content concentration: 56.1% by mass) (A)-2: Resin solution obtained in Synthesis Example 2 (solid content concentration: 41.7% by mass)

[0130] (Photopolymerizable monomer) (B)-1: Mixture of dipentaerythritol pentaacrylate and hexaacrylate (DPHA (acrylic equivalent: 96 to 115), manufactured by Nippon Kayaku Co., Ltd.) (B)-2: Mixture of pentaerythritol triacrylate and tetraacrylate (M-450 (acrylic equivalent: 88), manufactured by Toagosei Co., Ltd.) (B)-3: Dendritic polymer obtained in Synthesis Example 3 above

[0131] (Epoxy compounds) (C)-1: 3,4-epoxycyclohexanecarboxylate (3',4'-epoxycyclohexyl)methyl (Celloxide 2021P (epoxy equivalent: 135), manufactured by Daicel Corporation) (C)-2: 1,2-epoxy-4-(2-oxiranyl)cyclohexane adduct of 2,2-bis(hydroxymethyl)-1-butanol (EHPE3150 (epoxy equivalent: 180), manufactured by Daicel Corporation) (C)-3: butanetetracarboxylic acid tetra(3,4-epoxycyclohexylmethyl) modified ε-caprolactone (Epolead GT401 (epoxy equivalent 220), manufactured by Daicel Corporation)

[0132] [Metal oxide dispersion] (Titania dispersion) (D)-1: Titania dispersion (average particle size 50 nm) concentration 75 mass%, titania dispersion in propylene glycol monomethyl ether acetate solvent (D)-2: Titania dispersion (average particle size 120 nm) concentration 75 mass%, titania dispersion in propylene glycol monomethyl ether acetate solvent (D)-3: Titania dispersion (average particle size 270 nm) concentration 75 mass%, titania dispersion in propylene glycol monomethyl ether acetate solvent (D)-4: Titania dispersion (average particle size 410 nm) concentration 75 mass%, titania dispersion in propylene glycol monomethyl ether acetate solvent (D)-5: Titania dispersion (average particle size 620 nm) concentration 75 mass%, titania dispersion in propylene glycol monomethyl ether acetate solvent (D)-6: Titania dispersion (average particle size 970 nm) concentration 75 mass%, titania dispersion in propylene glycol monomethyl ether acetate solvent

[0133] (ZnO dispersion and ZrO2 dispersion) (D)-7: ZnO dispersion (average particle size 200 nm, refractive index 2.0) concentration 20 mass%, ZnO dispersion in propylene glycol monomethyl ether acetate solvent (D)-8: ZnO dispersion (average particle size 350 nm, refractive index 2.0) concentration 20 mass%, ZnO dispersion in propylene glycol monomethyl ether acetate solvent (D)-9: ZrO2 dispersion (average particle size 170 nm, refractive index 2.2) concentration 20 mass%, ZrO2 dispersion in propylene glycol monomethyl ether acetate solvent (D)-10: ZrO2 dispersion (average particle size 240 nm, refractive index 2.2) concentration 20 mass%, ZrO2 dispersion in propylene glycol monomethyl ether acetate solvent (D)-11: TiO2 dispersion (average particle size 400 nm, refractive index 2.5) concentration 75 mass%, TiO2 dispersion in propylene glycol monomethyl ether acetate solvent (D)-12: Al2O3 dispersion (average particle size 300 nm, refractive index 1.77) concentration 20 mass%, Al2O3 dispersion in propylene glycol monomethyl ether acetate solvent

[0134] (Photopolymerization initiator) (E): 1,2-octanedione, 1-[4-(phenylthio)phenyl]-, 2-(O-benzoyloxime) (IrgacureOXE-01, manufactured by BASF, "Irgacure" is a registered trademark of the company)

[0135] (solvent) (F)-1: Propylene glycol monomethyl ether acetate (PGMEA) (F)-2: Diethylene glycol ethyl methyl ether (EDM) (F)-3: 3-Methoxy-3-methyl-1-butyl acetate (MMBA) (F)-4: Methyl 3-methoxypropionate (MMP) (F)-5: Cyclohexanone (ANON)

[0136] (Hardening agent and hardening accelerator) (G)-1: Benzene 1,2,4-tricarboxylic acid-1,2-anhydride (G)-2: PGMEA solution containing 2.0% by mass of 1,8-diazabicyclo[5.4.0]undec-7-ene (DBU(R)), manufactured by San-Apro Co., Ltd.)

[0137] (Other additives) (H)-1: Surfactant (Megafac F-447, manufactured by DIC Corporation; "Megafac" is a registered trademark of the company) (H)-2: Surfactant (DOWSIL SH3775, manufactured by Dow, "DOWSIL" is a registered trademark of the company) (H)-3: Antioxidant (pentaerythritol tetrakis(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, Irganox1010, manufactured by BASF, "Irganox" is a registered trademark of the company) (H)-4: Coupling agent (3-glycidoxypropyltrimethoxysilane)

[0138] [Example 1] Photosensitive resin compositions using a titania dispersion as component (D) were prepared as Examples 1 to 16 and Comparative Examples 1 to 4. The blended components are shown in Tables 1 and 2. All values ​​in Tables 1 and 2 are in mass %. (B)-3 is the amount of dendritic polymer not including the solvent.

[0139] [Table 1]

[0140] [Table 2]

[0141] [evaluation] Using the photosensitive resin compositions of Examples 1 to 16 and Comparative Examples 1 to 4, substrates with cured films for evaluating development characteristics were produced.

[0142] (Preparation of substrate with cured film for evaluating development characteristics) The photosensitive resin compositions shown in Tables 1 and 2 were preliminarily exposed to a low-pressure mercury lamp at a wavelength of 254 nm and an illumination intensity of 1000 mJ / cm 2The coating was applied using a spin coater onto a 125 mm x 125 mm glass substrate "#1737" (manufactured by Corning Incorporated) (hereinafter referred to as "glass substrate") whose surface had been cleaned by irradiating it with ultraviolet light of 1000 nm so that the film thickness after heat curing treatment would be 2.0 μm, and the coating was prebaked using a hot plate at 90°C for 2 minutes to produce a cured film (coating). Next, a negative photomask with a line / space of 20 μm / 20 μm was placed on the cured film (coating), and a 30 mW / cm i-line illuminance was applied. 2 50mJ / cm with ultra-high pressure mercury lamp 2 The photocuring reaction was carried out by irradiating the resin with ultraviolet light.

[0143] Next, the exposed cured film (coating film) was soaked in a 0.04% potassium hydroxide solution at 25°C at 1 kgf / cm 2 After developing for 20 seconds from the development time (break time = BT) when the pattern begins to appear, the shower pressure was increased to 5 kgf / cm 2 The unexposed portions of the cured film (coating film) were removed to form a cured film pattern on the glass substrate, which was then main-cured (post-baked) at 90°C for 60 minutes using a hot air dryer to obtain substrates with cured films for evaluating development characteristics according to Examples 1 to 16 and Comparative Examples 1 to 4.

[0144] The following evaluations were carried out using the substrate with the cured film for evaluating the development characteristics.

[0145] [Development characteristic evaluation] (Pattern adhesion) (Evaluation method) After the main curing (post-baking), the 20 μm mask pattern was observed under an optical microscope.

[0146] (Evaluation Criteria) ○: No peeling at all △: Partially peeled off ×: Most of the area is peeled off

[0147] (Pattern linearity) (Evaluation method) After the main curing (post-baking), the 20 μm mask pattern was observed under an optical microscope.

[0148] (Evaluation Criteria) ○: No jagged edges are observed on the pattern edges. △: Jagged edges are observed in some areas of the pattern. ×: Jagged edges are observed in most of the pattern edges.

[0149] (Pattern definition) (Evaluation method) After the main curing (post-baking), the 10-50 μm mask pattern was observed under an optical microscope.

[0150] (Evaluation Criteria) ◎: A pattern of 10 to 15 μm is formed. ○: Patterns of 16 to 24 μm are formed △: Patterns of 25 to 50 μm are formed ×: No pattern is formed

[0151] Using the photosensitive resin compositions of Examples 1 to 16 and Comparative Examples 1 to 4, substrates with cured films for evaluating solvent resistance were produced.

[0152] (Preparation of substrate with cured film for evaluating solvent resistance) The photosensitive resin compositions shown in Tables 1 and 2 were applied onto a glass substrate using a spin coater so that the film thickness after heat curing treatment would be 2.0 μm, and the substrate was prebaked at 90° C. for 2 minutes using a hot plate to produce a cured film (coating). Next, a negative photomask with a line / space of 20 μm / 20 μm was placed on the cured film (coating), and an i-line illuminance of 30 mW / cm was applied. 2 50mJ / cm with ultra-high pressure mercury lamp 2 The photocuring reaction was carried out by irradiating the resin with ultraviolet light.

[0153] Next, the exposed cured film (coating film) was soaked in a 0.05% potassium hydroxide solution at 25°C at 1 kgf / cm 2After developing for 60 seconds with a shower pressure of 5kgf / cm 2 The unexposed portions of the cured film (coating film) were removed to form a cured film pattern on the glass substrate, which was then main-cured (post-baked) at 90°C for 60 minutes using a hot air dryer to obtain substrates with cured films for evaluating solvent resistance according to Examples 1 to 16 and Comparative Examples 1 to 4.

[0154] The following evaluations were carried out using the above-mentioned substrate with the cured film for evaluating solvent resistance.

[0155] [Solvent resistance evaluation] (Evaluation method) The surface of the cured film (coating film) formed on the glass substrate was rubbed back and forth 20 times in succession with a cloth soaked in PGMEA. A rating of △ or higher was deemed to be acceptable.

[0156] (Evaluation Criteria) ○: No dissolution or damage was observed on the surface of the cured film (coating film). △: Dissolution is observed in a small area of ​​the surface of the cured film (coating film), and there are also small scratches. ×: The surface of the cured film (coating film) is softened and most of it is scratched.

[0157] [Transmittance evaluation] (Evaluation method) The transmittance of the cured film-attached substrate in the visible light region (380 nm to 780 nm) was measured using a UV-Vis-NIR spectrophotometer "UH4150" (manufactured by Hitachi High-Tech Science Corporation). A grade of △ or higher was deemed to be acceptable.

[0158] (Evaluation Criteria) ○: Transmittance is 70% or more △: Transmittance is 60% or more and less than 70% ×: Transmittance is less than 60%

[0159] [Evaluation of light scattering] The substrate with the cured film was irradiated perpendicularly with white light, and the transmitted and scattered light was measured using a goniophotometer "GP-1" (manufactured by Nikka Densoku Co., Ltd.) Note that a grade of △ or higher was deemed to be acceptable.

[0160] (Evaluation Criteria) ○: The scattered light intensity at 5° and 60° is evaluated assuming that the angle of the directly transmitted light is 0°. The scattered light intensity at 60° is more than 20% of the scattered light intensity at 5°. △: The scattered light intensity at 5° and 60° is evaluated assuming that the angle of direct transmitted light is 0°. The scattered light intensity at 60° is more than 10% and 20% or less of the scattered light intensity at 5°. ×: The scattered light intensity at 60° is 10% or less of the scattered light intensity at 5° when the angle of the directly transmitted light is set to 0°.

[0161] The above-mentioned items were evaluated for the substrates with cured films obtained by curing the photosensitive resin compositions of Examples 1 to 16 and Comparative Examples 1 to 4, and the results are shown in Table 3.

[0162] [Table 3]

[0163] As is clear from the results of the above Examples 1 to 16 and Comparative Examples 1 to 4, it was found that by using a photosensitive resin composition containing the alkali-soluble resin represented by the general formula (1) of the present invention and TiO2, a substrate with a cured film that is excellent in light scattering properties and capable of forming a fine pattern can be prepared.

[0164] [Example 2] Photosensitive resin compositions using a titania dispersion as component (D) were prepared as Examples 17 to 30 and Comparative Examples 5 to 9. The blended components are shown in Tables 4 and 5. All values ​​in Tables 4 and 5 are in mass %. (B)-3 is the amount of dendritic polymer not including the solvent.

[0165] [Table 4]

[0166] [Table 5]

[0167] [evaluation] Using the photosensitive resin compositions of Examples 17 to 30 and Comparative Examples 5 to 9, substrates with cured films for evaluating development characteristics were produced.

[0168] (Preparation of substrate with cured film for evaluating development characteristics) The photosensitive resin compositions shown in Tables 4 and 5 were applied onto a glass substrate using a spin coater so that the film thickness after heat curing would be 2.0 μm, and the substrate was prebaked at 90° C. for 2 minutes using a hot plate to produce a cured film (coating). Next, the exposure gap was adjusted to 100 μm, and a negative photomask of 10 to 50 μm (in 5 μm increments) was placed on the cured film (coating), and an i-line illuminance of 30 mW / cm was applied. 2 50mJ / cm with ultra-high pressure mercury lamp 2 The photocuring reaction was carried out by irradiating the film with ultraviolet light.

[0169] Next, the exposed cured film (coating film) was soaked in a 0.04% potassium hydroxide solution at 25°C at 1 kgf / cm 2 After developing for 20 seconds from the development time (break time = BT) when the pattern begins to appear, the shower pressure was increased to 5 kgf / cm 2 The unexposed portions of the cured film (coating film) were removed to form a cured film pattern on the glass substrate, which was then main-cured (post-baked) at 230°C for 30 minutes using a hot air dryer to obtain substrates with cured films for evaluating development characteristics according to Examples 17 to 30 and Comparative Examples 5 to 9.

[0170] The following evaluations were carried out using the substrate with the cured film for evaluating the development characteristics.

[0171] [Development characteristic evaluation] (Pattern adhesion) (Evaluation method) After the main curing (post-baking), the 20 μm mask pattern was observed under an optical microscope.

[0172] (Evaluation Criteria) ○: No peeling at all △: Partially peeled off ×: Most of the area is peeled off

[0173] (Pattern linearity) (Evaluation method) After the main curing (post-baking), the 20 μm mask pattern was observed under an optical microscope.

[0174] (Evaluation Criteria) ○: No jagged edges are observed on the pattern edges. △: Jagged edges are observed in some areas of the pattern. ×: Jagged edges are observed in most of the pattern edges.

[0175] (Pattern definition) (Evaluation method) After the main curing (post-baking), the 10-50 μm mask pattern was observed under an optical microscope.

[0176] (Evaluation Criteria) ◎: A pattern of 10 to 15 μm is formed. ○: Patterns of 16 to 24 μm are formed △: Patterns of 25 to 50 μm are formed ×: No pattern is formed

[0177] [Transmittance evaluation] (Evaluation method) The transmittance of the substrate with the cured film in the visible light region (380 nm to 780 nm) was measured using a UV-Vis-NIR spectrophotometer "UH4150." A score of ◯ or higher was considered to be acceptable.

[0178] (Evaluation Criteria) ○: Transmittance is 70% or more △: Transmittance is 60% or more but less than 70% ×: Transmittance is less than 60%

[0179] Using the photosensitive resin compositions of Examples 17 to 30 and Comparative Examples 5 to 9, substrates with cured films for evaluating light scattering properties were produced.

[0180] (Preparation of substrate with cured film for evaluating light scattering properties) The photosensitive resin compositions shown in Tables 4 and 5 were applied onto a glass substrate using a spin coater so that the film thickness after heat curing treatment would be 2.0 μm, and the substrate was prebaked at 90° C. for 2 minutes using a hot plate to produce a cured film (coating film). Next, without covering the substrate with a negative photomask, the substrate was exposed to an i-line illuminance of 30 mW / cm. 2 50mJ / cm with ultra-high pressure mercury lamp 2 The photocuring reaction was carried out by irradiating the film with ultraviolet light.

[0181] Next, the exposed cured film (coating film) was soaked in a 0.05% potassium hydroxide solution at 25°C at 1 kgf / cm 2 After developing for 20 seconds from the development time (break time = BT) when the pattern begins to appear, the shower pressure was increased to 5 kgf / cm 2 The unexposed portions of the cured film (coating film) were removed to form a cured film pattern on the glass substrate, which was then main-cured (post-baked) at 230°C for 30 minutes using a hot air dryer to obtain substrates with cured films for evaluating light scattering properties according to Examples 17 to 30 and Comparative Examples 5 to 9.

[0182] The following evaluations were carried out using the above-mentioned substrate with the cured film for evaluating light scattering properties.

[0183] (Evaluation method) The substrate with the cured film was irradiated with white light perpendicularly, and the transmitted and scattered light was measured using a goniophotometer "GP-1." A grade of △ or higher was deemed to be acceptable.

[0184] (Evaluation Criteria) ○: The scattered light intensity at 5° and 60° is evaluated assuming that the angle of the directly transmitted light is 0°. The scattered light intensity at 60° is more than 20% of the scattered light intensity at 5°. △: The scattered light intensity at 5° and 60° is evaluated assuming that the angle of direct transmitted light is 0°. The scattered light intensity at 60° is more than 10% and 20% or less of the scattered light intensity at 5°. ×: The scattered light intensity at 60° is 10% or less of the scattered light intensity at 5° when the angle of the directly transmitted light is set to 0°.

[0185] The substrates with cured films obtained by curing the photosensitive resin compositions of Examples 17 to 30 and Comparative Examples 5 to 9 were evaluated for the above items. Table 6 shows the results.

[0186] [Table 6]

[0187] As is clear from the results of the above Examples 17 to 30 and Comparative Examples 5 to 9, it was found that by using a photosensitive resin composition containing the alkali-soluble resin represented by formula (1) of the present invention and TiO2, a substrate with a cured film that is excellent in light scattering properties and capable of forming a fine pattern can be prepared.

[0188] [Example 3] Photosensitive resin compositions using ZnO dispersion and ZrO2 dispersion as component (D) were prepared as Examples 31 to 45 and Comparative Examples 10 to 12. The blended components are shown in Tables 7 and 8. All values ​​in Tables 7 and 8 are in mass %. (B)-3 is the amount of dendritic polymer not including the solvent.

[0189] [Table 7]

[0190] [Table 8]

[0191] [evaluation] Using the photosensitive resin compositions of Examples 31 to 45 and Comparative Examples 10 to 12, substrates with cured films for evaluating development characteristics were produced.

[0192] (Preparation of substrate with cured film for evaluating development characteristics) The photosensitive resin compositions shown in Tables 7 and 8 were applied onto a glass substrate using a spin coater so that the film thickness after heat curing treatment would be 2.0 μm, and the substrate was prebaked at 90° C. for 2 minutes using a hot plate to produce a cured film (coating). Next, a negative photomask with a line / space of 20 μm / 20 μm was placed on the cured film (coating), and an i-line illuminance of 30 mW / cm was applied. 2 50mJ / cm with ultra-high pressure mercury lamp 2 The photocuring reaction was carried out by irradiating the resin with ultraviolet light.

[0193] Next, the exposed cured film (coating film) was soaked in a 0.04% potassium hydroxide solution at 25°C at 1 kgf / cm 2 After developing for 20 seconds from the development time (break time = BT) when the pattern begins to appear, the shower pressure was increased to 5 kgf / cm 2 The unexposed portions of the cured film (coating film) were removed to form a cured film pattern on the glass substrate, which was then main-cured (post-baked) at 90°C for 60 minutes using a hot air dryer to obtain substrates with cured films for evaluating development characteristics according to Examples 31 to 45 and Comparative Examples 10 to 12.

[0194] The following evaluations were carried out using the substrate with the cured film for evaluating the development characteristics.

[0195] [Development characteristic evaluation] (Pattern adhesion) (Evaluation method) After the main curing (post-baking), the 20 μm mask pattern was observed under an optical microscope.

[0196] (Evaluation Criteria) ○: No peeling at all △: Partially peeled off ×: Most of the area is peeled off

[0197] (Pattern linearity) (Evaluation method) After the main curing (post-baking), the 20 μm mask pattern was observed under an optical microscope.

[0198] (Evaluation Criteria) ○: No jagged edges are observed on the pattern edges. △: Jagged edges are observed in some areas of the pattern. ×: Jagged edges are observed in most of the pattern edges.

[0199] (Pattern definition) (Evaluation method) After the main curing (post-baking), the 10-50 μm mask pattern was observed under an optical microscope.

[0200] (Evaluation Criteria) ◎: A pattern of 10 to 15 μm is formed. ○: Patterns of 16 to 24 μm are formed △: Patterns of 25 to 50 μm are formed ×: No pattern is formed

[0201] Using the photosensitive resin compositions of Examples 31 to 45 and Comparative Examples 10 to 12, substrates with cured films for evaluating solvent resistance were produced.

[0202] (Preparation of substrate with cured film for evaluating solvent resistance) The photosensitive resin compositions shown in Tables 7 and 8 were applied onto a glass substrate using a spin coater so that the film thickness after heat curing treatment would be 2.0 μm, and the substrate was prebaked at 90° C. for 2 minutes using a hot plate to produce a cured film (coating). Next, a negative photomask with a line / space of 20 μm / 20 μm was placed on the cured film (coating), and an i-line illuminance of 30 mW / cm was applied. 2 50mJ / cm with ultra-high pressure mercury lamp 2 The photocuring reaction was carried out by irradiating the resin with ultraviolet light.

[0203] Next, the exposed cured film (coating film) was soaked in a 0.05% potassium hydroxide solution at 25°C at 1 kgf / cm 2 After developing for 60 seconds with a shower pressure of 5kgf / cm 2 The unexposed portions of the cured film (coating film) were removed to form a cured film pattern on the glass substrate, which was then main-cured (post-baked) at 90°C for 60 minutes using a hot air dryer to obtain substrates with cured films for evaluating solvent resistance according to Examples 31 to 45 and Comparative Examples 10 to 12.

[0204] The following evaluations were carried out using the above-mentioned substrate with the cured film for evaluating solvent resistance.

[0205] [Solvent resistance evaluation] (Evaluation method) The surface of the cured film (coating film) formed on the glass substrate was rubbed back and forth 20 times in succession with a cloth soaked in PGMEA. A rating of △ or higher was deemed to be acceptable.

[0206] (Evaluation Criteria) ○: No dissolution or damage was observed on the surface of the cured film (coating film). △: Dissolution is observed in a small area of ​​the surface of the cured film (coating film), and there are also small scratches. ×: The surface of the cured film (coating film) is softened and most of it is scratched.

[0207] [Transmittance evaluation] (Evaluation method) The transmittance of the substrate with the cured film in the visible light region (380 nm to 780 nm) was measured using a UV-Vis-Near Infrared Spectrophotometer "UH4150." In addition, a grade of △ or higher was considered to be acceptable. In addition, a grade of △ or higher was considered to be acceptable.

[0208] (Evaluation Criteria) ○: Transmittance is 80% or more △: Transmittance is 70% or more but less than 80% ×: Transmittance is less than 70%

[0209] [Evaluation of light scattering] The substrate with the cured film was irradiated with white light perpendicularly, and the transmitted and scattered light was measured using a goniophotometer "GP-1." A grade of △ or higher was deemed to be acceptable.

[0210] (Evaluation Criteria) ○: The scattered light intensity at 5° and 45° is evaluated assuming that the angle of the directly transmitted light is 0°. The scattered light intensity at 45° is more than 15% of the scattered light intensity at 5°. △: The scattered light intensity at 5° and 45° is evaluated assuming that the angle of direct transmitted light is 0°. The scattered light intensity at 45° is more than 10% and 15% or less of the scattered light intensity at 5°. ×: The scattered light intensity at 45° is 10% or less of the scattered light intensity at 5° when the angle of the directly transmitted light is set to 0°.

[0211] The substrates with cured films obtained by curing the photosensitive resin compositions of Examples 31 to 45 and Comparative Examples 10 to 12 were evaluated for the above items. Table 9 shows the results.

[0212] [Table 9]

[0213] As is clear from the results of the above Examples 31 to 45 and Comparative Examples 10 to 12, it was found that by using a photosensitive resin composition containing an unsaturated group-containing alkali-soluble resin of the general formula (1) of the present invention and a metal oxide (ZnO, ZrO2), it is possible to prepare a cured film that is excellent in light scattering properties and can form a fine pattern.

[0214] [Example 4] Photosensitive resin compositions using ZnO dispersion and ZrO2 dispersion as component (D) were prepared as Examples 46 to 60 and Comparative Examples 13 to 15. The blended components are shown in Tables 10 and 11. All values ​​in Tables 10 and 11 are in mass %. (B)-3 is the amount of dendritic polymer not including the solvent.

[0215] [Table 10]

[0216] [Table 11]

[0217] [evaluation] Using the photosensitive resin compositions of Examples 46 to 60 and Comparative Examples 13 to 15, substrates with cured films for evaluating development characteristics were produced.

[0218] (Preparation of substrate with cured film for evaluating development characteristics) The photosensitive resin compositions shown in Tables 10 and 11 were applied onto a glass substrate using a spin coater so that the film thickness after heat curing would be 2.0 μm, and the substrate was prebaked at 90° C. for 2 minutes using a hot plate to produce a cured film (coating). Next, the exposure gap was adjusted to 100 μm, and a negative photomask of 10 to 50 μm (in 5 μm increments) was placed on the cured film (coating), and the i-line illuminance was 30 mW / cm. 2 50mJ / cm with ultra-high pressure mercury lamp 2 The photocuring reaction was carried out by irradiating the film with ultraviolet light.

[0219] Next, the exposed cured film (coating film) was soaked in a 0.04% potassium hydroxide solution at 25°C at 1 kgf / cm 2 After developing for 20 seconds from the development time (break time = BT) when the pattern begins to appear, the shower pressure was increased to 5 kgf / cm 2 The unexposed portions of the cured film (coating film) were removed to form a cured film pattern on the glass substrate, which was then main-cured (post-baked) at 230°C for 30 minutes using a hot air dryer to obtain substrates with cured films for evaluating development characteristics according to Examples 46 to 60 and Comparative Examples 13 to 15.

[0220] The following evaluations were carried out using the substrate with the cured film for evaluating the development characteristics.

[0221] [Development characteristic evaluation] (Pattern adhesion) (Evaluation method) After the main curing (post-baking), the 20 μm mask pattern was observed under an optical microscope.

[0222] (Evaluation Criteria) ○: No peeling at all △: Partially peeled off ×: Most of the area is peeled off

[0223] (Pattern linearity) (Evaluation method) After the main curing (post-baking), the 20 μm mask pattern was observed under an optical microscope.

[0224] (Evaluation Criteria) ○: No jagged edges are observed on the pattern edges. △: Jagged edges are observed in some areas of the pattern. ×: Jagged edges are observed in most of the pattern edges.

[0225] (Pattern definition) (Evaluation method) After the main curing (post-baking), the 10-50 μm mask pattern was observed under an optical microscope.

[0226] (Evaluation Criteria) ◎: A pattern of 10 to 15 μm is formed. ○: Patterns of 16 to 24 μm are formed △: Patterns of 25 to 50 μm are formed ×: No pattern is formed

[0227] [Transmittance evaluation] (Evaluation method) The transmittance of the cured film-attached substrate in the visible light region (380 nm to 780 nm) was measured using a UV-Vis-NIR spectrophotometer "UH4150." A grade of △ or higher was deemed to be acceptable.

[0228] (Evaluation Criteria) ○: Transmittance is 80% or more △: Transmittance is 70% or more but less than 80% ×: Transmittance is less than 70%

[0229] Using the photosensitive resin compositions of Examples 46 to 60 and Comparative Examples 13 to 15, substrates with cured films for evaluating light scattering properties were produced.

[0230] (Preparation of substrate with cured film for evaluating light scattering properties) The photosensitive resin compositions shown in Tables 10 and 11 were applied onto a glass substrate using a spin coater so that the film thickness after heat curing would be 2.0 μm, and the substrate was prebaked at 90° C. for 2 minutes using a hot plate to produce a cured film (coating film). Next, without covering the substrate with a negative photomask, the substrate was exposed to an i-line illuminance of 30 mW / cm. 2 50mJ / cm with ultra-high pressure mercury lamp 2 The photocuring reaction was carried out by irradiating the film with ultraviolet light.

[0231] Next, the exposed cured film (coating film) was soaked in a 0.05% potassium hydroxide solution at 25°C at 1 kgf / cm 2 After developing for 20 seconds from the development time (break time = BT) when the pattern begins to appear, the shower pressure was increased to 5 kgf / cm 2 The unexposed portions of the cured film (coating film) were removed to form a cured film pattern on the glass substrate, which was then main-cured (post-baked) at 230°C for 30 minutes using a hot air dryer to obtain substrates with cured films for evaluating light scattering properties according to Examples 46 to 60 and Comparative Examples 13 to 15.

[0232] The following evaluations were carried out using the above-mentioned substrate with the cured film for evaluating light scattering properties.

[0233] [Evaluation of light scattering] (Evaluation method) A cured film (coating film) similar to the cured film (coating film) prepared for the solvent resistance evaluation was irradiated perpendicularly with white light, and the transmitted and scattered light was measured using a goniophotometer.

[0234] (Evaluation Criteria) ○: The scattered light intensity at 5° and 45° is evaluated assuming that the angle of the directly transmitted light is 0°. The scattered light intensity at 45° is more than 15% of the scattered light intensity at 5°. △: The scattered light intensity at 5° and 45° is evaluated assuming that the angle of direct transmitted light is 0°. The scattered light intensity at 45° is more than 10% and 15% or less of the scattered light intensity at 5°. ×: The scattered light intensity at 45° is 10% or less of the scattered light intensity at 5° when the angle of the directly transmitted light is set to 0°.

[0235] The substrates with cured films obtained by curing the photosensitive resin compositions of Examples 46 to 60 and Comparative Examples 13 to 15 were evaluated for the above items. The results are shown in Table 12.

[0236] [Table 12]

[0237] As is clear from the results of Examples 46 to 60 and Comparative Examples 13 to 15, it was found that by using a photosensitive resin composition containing an unsaturated group-containing alkali-soluble resin of the general formula (1) of the present invention and a metal oxide (ZnO, ZrO2), a cured film that is excellent in light scattering properties and can form a fine pattern can be prepared. [Industrial Applicability]

[0238] According to the method for producing a substrate with a cured film of the present invention, a substrate with a cured film having excellent light scattering properties can be obtained. Therefore, it is useful for, for example, a display device. That is, since a pattern can be formed by photolithography, it has an advantage that it can be formed by an existing photolithography process. In addition, since film strength can be obtained even at low temperatures, it is suitable for producing touch panels and color filters using substrates with low heat resistance.

Claims

[Claim 1] The method for producing a substrate with a cured film by forming a cured film pattern having light scattering properties on a substrate comprises applying a photosensitive resin composition containing inorganic particles having an average particle size of 100 to 700 nm onto the substrate, exposing the composition through a photomask, removing unexposed areas by development, and heating the substrate to form a predetermined cured film pattern.

Citation Information

Patent Citations

  • Photosensitive composition, pattern, and display device having pattern

    JP2013156304A

  • Resin composition for light scattering layer, light scattering layer, and organic electroluminescent device

    JP2015022794A

Cited By

  • Laminate

    WO2026141505A1